2021
DOI: 10.3390/ijms222313057
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of TCA Cycle-Related Enzymes in Human Diseases

Abstract: The tricarboxylic acid (TCA) cycle is the main source of cellular energy and participates in many metabolic pathways in cells. Recent reports indicate that dysfunction of TCA cycle-related enzymes causes human diseases, such as neurometabolic disorders and tumors, have attracted increasing interest in their unexplained roles. The diseases which develop as a consequence of loss or dysfunction of TCA cycle-related enzymes are distinct, suggesting that each enzyme has a unique function. This review aims to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 104 publications
(142 reference statements)
1
18
1
Order By: Relevance
“…Aging and metabolic diseases such as type 2 diabetes are closely associated with a decrease in the mitochondrial capacity including the TCA cycle activities (7)(8)(9)(10), which could lead to the disruption of nutrient metabolism and a shortage of cellular energy. Recent studies have reported that the dysfunction of the TCA cycle along with a loss or a decrease in the activity of its related enzymes is involved in the etiology of various diseases (11). However, the effects of such TCA cycle impairment on the flexibility and capacity of substrate metabolism in the heart and skeletal muscles have not yet been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Aging and metabolic diseases such as type 2 diabetes are closely associated with a decrease in the mitochondrial capacity including the TCA cycle activities (7)(8)(9)(10), which could lead to the disruption of nutrient metabolism and a shortage of cellular energy. Recent studies have reported that the dysfunction of the TCA cycle along with a loss or a decrease in the activity of its related enzymes is involved in the etiology of various diseases (11). However, the effects of such TCA cycle impairment on the flexibility and capacity of substrate metabolism in the heart and skeletal muscles have not yet been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The TCA cycle is able to produce ATP as well as NADH and FADH2 during the oxidization of acetyl-coenzyme A (acetyl-CoA). 25 The NADH and FADH2 produced from TCA cycle then further feed the ETC complex I (NADH dehydrogenase) and complex II (succinate dehydrogenase), respectively. The two complexes then transfer their electrons through the ETC and eventually generate ATP via oxidative phosphorylation (OXPHOS).…”
Section: Cellular Respiration and Atp Synthesismentioning
confidence: 99%
“…Cancer cells are characterized by metabolic and epigenetic changes in TCA cycle enzymes that correlate with disease progression. Therefore, some enzymes have become a potential therapeutic target, but a limitation is the high toxicity of the tested compounds [ 200 , 201 ].…”
Section: The Krebs Cyclementioning
confidence: 99%